2006
DOI: 10.1002/chem.200501015
|View full text |Cite
|
Sign up to set email alerts
|

Supported Absorption of CO2 by Tetrabutylphosphonium Amino Acid Ionic Liquids

Abstract: A new type of "task specific ionic liquid", tetrabutylphosphonium amino acid [P(C4)4][AA], was synthesized by the reaction of tetrabutylphosphonium hydroxide [P(C4)4][OH] with amino acids, including glycine, L-alanine, L-beta-alanine, L-serine, and L-lysine. The liquids produced were characterized by NMR, IR spectroscopies, and elemental analysis, and their thermal decomposition temperature, glass transition temperature, electrical conductivity, density, and viscosity were recorded in detail. The [P(C4)4][AA] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
439
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(459 citation statements)
references
References 23 publications
19
439
1
Order By: Relevance
“…approach that retains the advantages of a liquid absorbant is to tether an amine functionality to either the cation [24] or anion [25] fragment of an ionic liquid. [26,27] In these nonaqueous environments, the exact nature of the amine-CO 2 reaction is not as well understood, and optimization of these materials is largely empirical.…”
Section: Introductionmentioning
confidence: 99%
“…approach that retains the advantages of a liquid absorbant is to tether an amine functionality to either the cation [24] or anion [25] fragment of an ionic liquid. [26,27] In these nonaqueous environments, the exact nature of the amine-CO 2 reaction is not as well understood, and optimization of these materials is largely empirical.…”
Section: Introductionmentioning
confidence: 99%
“…1.5.B). 55 To determine various amine vapors, the [P6, 6,6,14]3HPTS film are fabricated by spin casting on the surface of glass slides made hydrophobic by derivatization with propyltrichlorosilane. 49 Note that in the latter two materials, the anions of the used task-specific ILs interact with analytes.…”
Section: ·2 Materials Varieties and Preparation Methodsmentioning
confidence: 99%
“…1.5.B) fast and reversibly absorbed CO2 because of the interaction between CO2 and anions of ILs. 55 Liu et al 51 and Tian et al 53 developed specially designed CO2 chemosensors based on a novel photophysical effect aggregation-induced emission. Carbamate and amidine ILs that were the products of the reactions between CO2 and dipropylamine 51 or amidinebased compounds 53 increased viscosity and polarity of the reaction media.…”
Section: ·6 Other Functionsmentioning
confidence: 99%
“…It is reported that the capture of CO 2 alone will increase the energy requirements of a plant by 25%-40% [3]. Therefore, many scientists all over the world are focusing on the investigations of the environment-friendly capture technology with higher efficiency and lower energy consumption compared with the current technologies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the corrosion, volatility, toxicity of the amines, and their high regeneration energy requirement in the applications, in recent years, scientists all over the world have designed and synthesized many ionic liquids (ILs) as absorbents to absorb and separate CO 2 from the gas mixtures [5][6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The IL-based CO 2 capture technology is considered to be a promising and competitive way to separate CO 2 because of its advantages of non-volatility, recycling, environment-friendliness, functionality, and high efficiency of CO 2 capture [9].…”
Section: Introductionmentioning
confidence: 99%